Macro-economics, markets and the humid forests of Cameroon, 1967-1997 - Ndoye, O.; Kaimowitz, D. (2000)
The paper analyses how macro-economic and agricultural policies, market fluctuations and demographic changes affected forests in the Humid Forest Zone of Cameroon in four periods between 1967 and 1997. For each period it examines how these variables influenced cocoa, coffee, food, and agro-industrial crop production and area, and logging. It concludes that government policies, market fluctuations and demographic changes all had a strong impact on forests. Pressure on forests increased after structural adjustment policies were initiated in the mid- 1980s. Malthusian reasoning alone cannot explain the level of deforestation and forest degradation in Cameroon.